Comprehensive analysis of transcriptome-wide m6A methylome in the lung tissues of mice with acute particulate matter exposure - Juan Song; Yingying Zeng; Mengchan Zhu; Guiping Zhu; Cuicui Chen; Meiling Jin; Jian Wang; Yuanlin Song (Ecotoxicology and Environmental Safety, 2022)
Particulate matter (PM) exposure is identified as a critical risk factor for chronic airway diseases, but the biological mechanism of PM-induced lung damage was not fully elucidated. The m6A methylation, as the main member of epigenetic modifications, has been found to play an important role in different pulmonary diseases, but its regulatory effect on PM-induced lung damage remains unknown. This study firstly used the methylated RNA immunoprecipitation sequencing (MeRIP-seq) to reveal the m6A methylome profiles in the lung tissues of mice with acute PM exposure. Compared with the normal control, a total of 2210 differentially hypermethylated m6A peaks within 1879 genes and 1278 differentially hypomethylated m6A peaks within 1153 genes were identified in the PM-exposed group. Conjoint analysis of MeRIP-seq and high-throughput sequencing for RNA (RNA-seq) data predicated several potential pathways including MAPK signaling pathway, cell senescence, and cell cycle. Four m6A-modified differentially expressed genes (IL-1a, IL-1b, ADAM-8, and HMOX-1) were selected for validation using MeRIP-qPCR. Furthermore, the m6A-modified IL-1a promoted PM-induced inflammation via regulating MAPK signaling pathway. These results provide a new insight into the biological mechanism of PM-induced lung damage, and help us to develop new methods to prevent and treat PM-induced adverse health effects.